Penerapan Pemberian Terapi Foot Massage dengan Minyak Zaitun terhadap Penurunan Tingkat Keletihan pada Ny. J dengan CKD di Ruangan Hemodialisa RSUD Gunung Jati Cirebon - Yusminarti Yusminarti; Dewi Erna Marisa; Muadi Muadi (STIKES Columbia Asia Medan, 2026)
Fatigue is a common symptom experienced by many patients undergoing hemodialysis, whether due to situational, physiological, or long-term factors. Foot massage is the manipulation of connective tissue by rubbing, squeezing, or patting, which improves circulation, improves muscle tone, and provides a relaxing effect. The purpose of this study was to determine the application of foot massage therapy with olive oil to reduce fatigue levels in patients with chronic kidney disease (CKD) undergoing hemodialysis. This study used a pre-test-post-test case study design. The sampling consisted of two respondents who met the inclusion criteria. The instrument used was the 13-question Functional Assessment of Chronic Illness Therapy-Fatigue Scale (FACIT-Fatigue Scale) questionnaire, administered before and after the intervention.The study found that patients experienced changes in fatigue levels after receiving foot massage therapy with olive oil for two days. The fatigue level changed from an initial score of 32-23 (severe-moderate) to 18-13 (moderate-mild) on the first day. On the second day, the score decreased from 19-18 (moderate) to 16-14 (mild).